SECONDARY SCHOOL STUDENTS' PERCEPTIONS OF ONLINE LEARNING DURING COVID-19: EFFECTS ON MENTAL WELLBEING AND LEARNING DIFFICULTIES (International Journal of Food and Nutritional Sciences, 2021)
Establishing the scene. Learning requires full involvement and focus from students. The COVID-19 epidemic has led to a surge in online education, which could have an impact on students' ability to focus and pay attention, especially those who have unique learning challenges. Aims. 1. Compared to classroom instruction, students' ratings of their online learning experience would be poorer across the board. 2. Individuals with certain learning disabilities may have a more pronounced decline in focus, engagement, perceived learning, and selfworth as a result of online learning as contrasted to classroom education. 3. A decline in student experience ratings as a result of online learning is linked to worse mental health. Sample. Four hundred seven students from ages eleven to eighteen in a Welsh secondary school. Methods. During the first UK national lockdown (March 2020–July 2020), students were asked to reflect on their learning experiences both in and out of the classroom. End result. There was a statistically significant difference between online and classroom learning in terms of students' learning experiences (focus, engagement, capacity to learn, and self-worth). Among pupils who had identified learning disabilities, these distinctions stood out more. Mental health was also linked to how well one felt they could study and participate in both traditional classroom settings and online learning environments.